The Effectivity of Losartan Tablet for Decreasing Fibrotic Tissue Formation in Gastrocnemius Muscle Injury Grade I of Rabbits - Boby Harul Priono; Hermawan Rasyid; Yoyos Ismiarto; Ahmad Ramdan (Pharmaceutical Sciences and Research, 2019)
ABSTRACT